THE ROLE OF INDEPENDENT WORK OF STUDENTS IN THE EDUCATIONAL PROCESS - Abduvalieva, Ezoza (Журнал иностранных языков и лингвистики, 2021)
This article is about the role of independent work of students in the educational process. It analyzes the increase of the motivation of students to learn discipline.